Social Recipes. Forms of Culinary-doing Between Instagram and Tik Tok - Sanfilippo , Maddalena (E|C, 2023)
In this paper, we discuss about the phenomenon of intersemiotic translation of recipe genre within digital media, with specific reference to audiovisual content produced by food influencers in social media. After examining studies on the semiotics of taste in relation to recipe and the relationship between the Internet and cuisine, we focus on the analysis of a group of social video-recipes. The objective is to understand, through a socio- semiotic comparative analysis, the dialogue between the language of digital media and the culinary system, aiming to identify the mechanisms of signification that characterize this part of contemporary gastronomic discourse.